The Evolution of Asset Pricing Theory: A Systematic Literature Review - Siti Epa Hardiyanti (PT Larva Wijaya Penerbit, 2026)
Asset Pricing Theory has undergone substantial transformation since the introduction of Modern Portfolio Theory by Markowitz on 1952. Its evolution subsequently progressed through the development of Capital Asset Pricing Model (CAPM), Arbitrage Pricing Theory (APT), Intertemporal Capital Asset Pricing Model (I-CAPM), Consumption Based Capital Asset Pricing Model (C-CAPM), Sustainable Capital Asset Pricing Model (S-CAPM), and contemporary of Multifactor frameworks such as Fama-French Factor Models (FF3F, FF5F, FF6F). Although these models offer distinct theoritical perspectives, they share a common objective: to explain the relationship between risk and return more accurately. However, variations in market structures, the emergence of empirical anomalies, and the rapid growth of digital assets have challenged the explanatory power and validity of several traditional asset pricing models. Consequently, this Systematic Literature Review (SLR) aims to map the evolution of asset pricing theory, examine the theoritical fondations of major asset pricing frameworks, identify existing research gaps, and propose directions for future scholarly inquiry. The findings suggest that no single asset pricing model is capable of universally explaining variations in asset returns across all market environments. Furthermore, the rise of digital assets and advances in big data analytics highlight the needed for new generation of asset pricing theories that are more adaptive to the complexities and dynamics of contemporary financial markets.